Analisis Landasan Pengembangan Kurikulum PAI dalam Perspektif Pendidikan Islam - Legita Pramesti; Ma’mun Hanif; Nabila Imtiyas Ramadhani; Zahra Kameliana; Muhammad Khafidz Alfaza (Yayasan Al-Afif, 2026)
The development of the Islamic Religious Education (IRE) curriculum plays a significant role in achieving educational goals, specifically by focusing on the intellectual, spiritual, moral, and social development of students. Therefore, the purpose of this article is to discuss and explore the foundations of the PAI curriculum from the perspective of Islamic Education. These foundations encompass philosophical, legal, conceptual, psychological, and sociological aspects. This study employs a qualitative approach using library research, with sources drawn from books, articles, and scientific journals. The analysis technique used is content analysis to identify the main concepts in the development of the PAI curriculum. The results of the study indicate that each foundation is interconnected in shaping a systematic PAI curriculum that is relevant to students’ needs. Thus, the development of the PAI curriculum is expected to foster students who are faithful, possess noble character, and are adaptable to the changing times without compromising Islamic values.